Participation of the Theological Faculty of Sofia University "St. Kliment of Ochrid" in the Second Conference of the International Orthodox Theological Association (IOTA) (Forum Theologicum Sardicense, 2025)
The article presents the participation of professors, PhD students, and students from the Theological Faculty of Sofia University in the Second Congress of the International Association of Orthodox Theology (IOTA) held in Volos, Greece, in 2023.
Keywords: Orthodox Theology; Theological Education; Orthodox Church